2000
DOI: 10.2118/62507-pa
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of Wettability, Initial Water Saturation, Aging Time, and Oil Recovery by Spontaneous Imbibition and Waterflooding

Abstract: Previous studies of crude oil/brine/rock ͑COBR͒ and related systems showed that wettability and its effect on oil recovery depend on numerous complex interactions. In the present work, the wettability of COBR systems prepared using Prudhoe Bay crude oil, a synthetic formation brine, and Berea Sandstone was varied by systematic change in initial water saturation and length of aging time at reservoir temperature ͑88°C͒. All displacement tests were run at ambient temperature. Various degrees of water wetness were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(115 citation statements)
references
References 18 publications
7
108
0
Order By: Relevance
“…The wettability of cores could be changed by saturating cores with crude oil and aging under high temperature (Buckley et al, 1998;Standnes, 2000;Loahardjo et al, 2010). The different wettability could be obtained by different aging time and temperature (Zhou et al, 2000). Water or surfactant solution is drawn into the core by SI.…”
Section: Imbibition Cells and Weighing Methodsmentioning
confidence: 99%
“…The wettability of cores could be changed by saturating cores with crude oil and aging under high temperature (Buckley et al, 1998;Standnes, 2000;Loahardjo et al, 2010). The different wettability could be obtained by different aging time and temperature (Zhou et al, 2000). Water or surfactant solution is drawn into the core by SI.…”
Section: Imbibition Cells and Weighing Methodsmentioning
confidence: 99%
“…Zhou et al (2000) showed that with increase in the aging time, the scaled spontaneous imbibition became slower indicating decreased water-wetness. Four cores were used to test the effect of aging time.…”
Section: Aging Timementioning
confidence: 99%
“…Many parameters such as crude oil properties, initial water saturation, aging time, aging temperature, core preparation procedure, etc., can be adjusted to achieve a spectrum of wettability (Zhou et al, 2000;Xie and Morrow, 2001;Tie et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Wettability is a major factor that controls multiphase fluid flow, location and distribution of fluids in a reservoir [3]. It has been well recognized that reservoir wettability significantly influences oil production during primary, secondary, and tertiary recovery (enhanced oil recovery) stages [4][5][6].…”
Section: Introductionmentioning
confidence: 99%